Learning in Digital Networks – ICT literacy: A novel assessment of students' 21st century skills. (June 2017) - Siddiq, Fazilat; Gochyyev, Perman; Wilson, Mark
Abstract: The present investigation aims to fill some of the gaps revealed in the literature regarding the limited access to more advanced and novel assessment instruments for measuring students' ICT literacy. In particular, this study outlines the adaption, further development, and validation of the Learning in Digital Networks—ICT literacy (LDN-ICT) test. The LDN-ICT test comprises an online performance-based assessment in which real-time student-student collaboration is facilitated through two different platforms (i.e., GoogleDocs and chat). The test attempts to measure students' ability in handling digital information, to communicate and collaborate during problem solving. The data are derived from 144 students in grade 9 analyzed using item response theory models (unidimensional and multidimensional Rasch models). The appropriateness of the models was evaluated by examining the item fit statistics. To gather validity evidence for the test, we investigated the differential item functioning of the individual items and correlations with other constructs (e.g., self-efficacy, collective efficacy, perceived usefulness and academic aspirations). Our results supported the hypothesized structure of LDN-ICT as comprising four dimensions. No significant differences across gender groups were identified. In support of existing research, we found positive relations to self-efficacy, academic aspirations, and socio-economic background. In sum, our results provide evidence for the reliability and validity of the test. Further refinements and the future use of the test are discussed. Highlights: The Learning in Digital Networks (LDN-ICT) test is comprised of multiple dimensions. Multidimensional Rasch model shows better fit than Unidimensional Rasch model. Evidence for reliability and validity of the LDN-ICT test is established. LDN-ICT is positively related to students' self-efficacy and academic aspirations. Differences in LDN-ICT across socio-economic status exit, yet not across gender.